2019
DOI: 10.1186/s12889-019-7161-y
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial for overweight and obesity in preschoolers: the More and Less Europe study - an intervention within the STOP project

Abstract: Background: Childhood overweight and obesity is a serious public health issue with an increase being observed in preschool-aged children. Treating childhood obesity is difficult and few countries use standardized treatments. Therefore, there is a need to find effective approaches that are feasible for both health care providers and families. Thus, the overall aim of this study is to assess the acceptance and effectiveness of a parent support program (the More and Less, ML) for the management of overweight and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 61 publications
(80 reference statements)
0
24
0
2
Order By: Relevance
“…Longitudinal studies depicted trends in eating behaviours and socioeconomic factors that influence the obesity prevalence 57 and interventions for weight management in adolescents. 31 The major limitations of our study are the small sample size, the retrospective data collection, the patients' age heterogeneity, and the relatively short follow-up duration. The retrospective data collection also contributes to the small sample because not all evaluated data were available in the medical charts.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Longitudinal studies depicted trends in eating behaviours and socioeconomic factors that influence the obesity prevalence 57 and interventions for weight management in adolescents. 31 The major limitations of our study are the small sample size, the retrospective data collection, the patients' age heterogeneity, and the relatively short follow-up duration. The retrospective data collection also contributes to the small sample because not all evaluated data were available in the medical charts.…”
Section: Discussionmentioning
confidence: 95%
“…20 A randomized-control trial based on a parent-support program for pediatric obesity is in progress since July 2019 in Romania, Spain, and Sweden. 31 Motivational interviewing has been shown to be effective in pediatric obesity management. 32 Previous cross-sectional studies have shown that metabolic and hormonal changes accompany weight excess, but no longitudinal study has evaluated this relationship as provided by Romanian screening for obesity-related comorbidities guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…In Romania the authors demonstrated a statistically significant decrease in fruit juice consumption after the intervention, however this was not maintained on follow-up. Another initiative, the More and Less Europe study [71] aimed at preschoolers, proposes a slightly different approach, including a parent support program with group sessions, followed by a 6-month period of support by means of a mobile application. Recruitment has started in 2019 and results are pending.…”
Section: Discussionmentioning
confidence: 99%
“…The current orientation for improving adherence to treatments in pediatrics focuses on motivation, problem-solving skills, and reduction of post-treatment influence, resorting to a number of tools including web-based programs [6,7], "exergaming" [8][9][10], school interventions [11], summer camp [12], parent engagement [13][14][15], and automated mobile technology (MT) [16][17][18][19][20][21][22][23][24]. Studies focused on mobile phone interventions to improve lifestyle and preventing overweight and obesity are attracting interest in both the adult and pediatric population.…”
Section: Introductionmentioning
confidence: 99%